On some Brazilian plants distributed by Martius in 1827 and published by Colla in Herbarium Pedemontanum- v - De Moraes, Pedro Luís Rodrigues [UNESP]; De Smedt, Sofie; Guglielmone, Laura (My University, 2014)
In volume V of Herbarium Pedemontanum, Luigi Colla cited 21 species based on Brazilian specimens distributed by Carl Martius in 1827. Of them, 18 were treated as new species. The original material examined by Colla (now held at TO) was found and compared with duplicates held elsewhere. Material was located for all but two of the taxa described by Colla. Fourteen hitherto unresolved species names are here clarified, and seventeen new synonymies, eighteen lectotypifications, one neotypification, and one new combination are proposed. Based on the collecting localities and comparison with specimens at Herbarium Martii at BR and elsewhere, at least sixteen of the specimens distributed by Martius could be attributed to Prince Maximilian zu Wied.
Keywords: Brazil; Herbarium Pedemontanum; Historical collections; Maximilian; Nomenclature; Prince of Wied; Taxonomy